Pendampingan Pengembangan Website Official PT Mond Nature Lestari untuk Penyebaran Informasi Produk - Priyatno, Arif Mudi; Sudirman, Wahyu Febri Ramadhan; Lasepa, Wanda; Afrinis, Nur; Rizqi, Eka Roshifita; Tanjung, Lailatul Syifa; Rusnedy, Hidayati (Journal of Digital Community Services, 2024)
The efficient distribution of product information plays a crucial role in the growth of inclusive and sustainable micro-enterprises. Within this framework, the community service activity is undertaken to enhance the accessibility of product information from PT Mond Nature Lestari. This is achieved by supporting the development of PT Mond Natural LESTARI's official website. PT Mond Nature Lestari is a small business established on August 18, 2020, with the NIB (Manduk Enterprise Number) 0220307891283. This endeavor centers on the manufacturing of teas, namely teas and flour, derived from natural and premium-grade components. This community service is implemented using a systematic support approach, encompassing requirements assessment, establishment of support teams, training, website building, content management training, and technical assistance. The escort team comprises IT specialists, web developers, and facilitators. The outcome of this community service endeavor is the development of an operational and adaptable official website for Mond Nature Lestari. The website provides convenient access to crucial information, including the items offered by PT Mond Nature Lestari. The support and training provided significantly enhanced the human resource capability at Mond Nature Lestari in autonomously managing and updating website material. The primary goal of enhancing the accessibility of Mond Nature Lestari's information products has been effectively accomplished through this community service. This community service activity has resulted in a favorable transformation in the way communication and micro-enterprise growth occur, moving towards a more sophisticated, interconnected, and inclusive approach.